1994
DOI: 10.1177/154079699401900308
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Placement of Students with Severe Disabilities in General Education versus Special Classes

Abstract: This program evaluation study was designed to investigate the effects of the placement of students with severe disabilities in general education versus special education classes. Sixteen elementary education programs in California participated. Eight represented the "full inclusion" model of integration, and eight represented the special class model. Two students were selectedfrom each program, with one ofthe students experiencing more disability and the other student experiencing less disability. A number ofk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 15 publications
3
83
0
2
Order By: Relevance
“…However, Budoff and Gottlieb (1976) Table 4 for an analysis of methodological issues related to each study.) Hunt, Farron-Davis, Beckstead, Curtis, and Goetz (1994) (Fryxell & Kennedy, 1995) and 12-to 14-year-olds (Kennedy, Shukla, & Fryxell, 1997). Both studies showed that the students in general education classrooms had significantly more social contacts and interaction with nondisabled peers than did the children in the special class.…”
Section: Within-group (Mr) Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…However, Budoff and Gottlieb (1976) Table 4 for an analysis of methodological issues related to each study.) Hunt, Farron-Davis, Beckstead, Curtis, and Goetz (1994) (Fryxell & Kennedy, 1995) and 12-to 14-year-olds (Kennedy, Shukla, & Fryxell, 1997). Both studies showed that the students in general education classrooms had significantly more social contacts and interaction with nondisabled peers than did the children in the special class.…”
Section: Within-group (Mr) Studiesmentioning
confidence: 96%
“…Thus, as shown in Kanagawa, 1994;Brinker, 1985;Cole & Meyer, 1991;Fryxell & Kennedy, 1995;Hunt et al, 1994;Kennedy & Itkonen, 1994;Kennedy et al, 1997;Walker, 1974 (Espiner et al, 1985;Ferencz-Stager & Young, 1981;Gilkey & Zetlin, 1987;Gottlieb & Budoff, 1973 (Luckasson et al, 1992). Thus, it is important to recognize the relevance of historical trends in making research interpretations or for changing practice (Polloway, 1984 …”
Section: Within-group (Mr) Studiesmentioning
confidence: 99%
“…Inclusion proponents have insisted that students with disabilities would learn better academically and socially in general education classroom. Socially, students with and without disabilities would experience more balanced friendships in the inclusive settings, and academically, students with disabilities would acquire more academic knowledge through the effective general education teacher instruction because general education teachers were the ones certified to teach academics (Grider, 1995;Hartzell, Liaupsin, Gann, & Clem, 2015;Hunt, Farron-Davis, Beckstead, Curtis, & Goetz, 1994;Mather & Robers, 1994). In other words, inclusion proponents believed that general education settings were the best educational setting to provide "appropriate education" to students both with and without disabilities.…”
Section: Two Perspectives On "Appropriate" Educationmentioning
confidence: 99%
“…There is a limited research base regarding the impact of physical classroom arrangement on educational outcomes. Hunt, Farron-Davis, Beckstead, Curtis, and Goetz (1994) compared 16 students who were fully included in the general education classroom with 16 students in self-contained special education classrooms. One of their findings was that students receiving special services were grouped more often with peers (i.e., entire group or divided group physical classroom arrangement) in the general education classroom than students receiving services in the special education classroom.…”
Section: Practitioners Often Interpret Promoting "Access To Thementioning
confidence: 99%